Fabulating in the Square: the Creation of Literary and Ludics Spaces in the Festival of The Book and Literature in São Miguel Paulista - Carvalho, Helba (Linha D'Água, 2017)
The aim of this work is to show the results of a practical experience of motivation to reading literature texts in projects I have coordinated for four years with the students of the Literature course from Universidade Cruzeiro do Sul, in the Festival of the Book and Literature in São Miguel Paulista. All the proposed activities in the event aim at recovering the oral tradition of storytelling and “ the art of re-telling them over and over again”, according to Walter Benjamin (1994) and re-signifying them in the public space (the square) where the Festival takes place, transforming it in a ludic space with literary and artistic interventions that could promote transformations or reactions which may have an intelectual, sensorial or physical impact in the audience, comprised mostly of students from public and private schools in the East side of São Paulo. In this sense, the future teacher, who is also a student from the Literature course, has the opportunity to relate to youngsters and children for three days in a different space from the school environment, creating situations of interaction that demand their knowledge about literature, a taste for literature, creativity, teamwork and interaction to the public and, above all, social responsibility associated to the proposed activities, aiming at raising awareness of the audience by means of literature.